2004
DOI: 10.1086/382876
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak ofAeromonas hydrophilaWound Infections Associated with Mud Football

Abstract: On 16 February 2002, a total of 26 people presented to the emergency department of the local hospital in the rural town of Collie in southwest Western Australia with many infected scratches and pustules distributed over their bodies. All of the patients had participated in a "mud football" competition the previous day, in which there had been ~100 participants. One patient required removal of an infected thumbnail, and another required surgical debridement of an infected toe. Aeromonas hydrophila was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 15 publications
1
55
0
4
Order By: Relevance
“…Ribeiro et al (2010) Aeromonas species are the most common organisms reported in infections of burns exposed to contaminated water. However, Lamy et al Polluted aquatic environments can be considered a source of contamination for recreational waters and water used in the irrigation process (Villari et al 2000;Davies et al 2001;Uyttendaele et al 2004;Vally et al 2004;Villarruel-Ló pez et al 2005;Daskalov 2006;Dwivedi et al 2008). Besides the determination of indicator bacteria, it is important to understand the distribution of potentially doi: 10.2166/wh.2010.140 pathogenic bacteria in a given ecosystem that could affect natural water used for human contact or consumption (Nagvenkar & Ramaiah 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al (2010) Aeromonas species are the most common organisms reported in infections of burns exposed to contaminated water. However, Lamy et al Polluted aquatic environments can be considered a source of contamination for recreational waters and water used in the irrigation process (Villari et al 2000;Davies et al 2001;Uyttendaele et al 2004;Vally et al 2004;Villarruel-Ló pez et al 2005;Daskalov 2006;Dwivedi et al 2008). Besides the determination of indicator bacteria, it is important to understand the distribution of potentially doi: 10.2166/wh.2010.140 pathogenic bacteria in a given ecosystem that could affect natural water used for human contact or consumption (Nagvenkar & Ramaiah 2009).…”
Section: Introductionmentioning
confidence: 99%
“…watering facility, pond water and animals) at the studied zoo in our previous study (Kim et al, 2015a). These species of bacteria commonly infect the skin through exposure to contaminated water or soil, but, typically, are not directly associated with the formation of skin lesions (Kelly et al, 1993;Vally et al, 2004). Thus, the authors believe that demodicosis occurred primarily and the secondary bacterial infection developed through lesions associated with demodicid mites.…”
Section: Discussionmentioning
confidence: 93%
“…In areas commonly frequented by animals, topsoil used to make slurry fields can be contaminated with faeces from ruminants or wild animals [1][2][3][4][5][6][7]. Multiple exposures to mud can occur in this kind of sport events [2][3][4][5][6][7][8][9]. Mud is an efficient vehicle for pathogenic microorganisms [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mud is an efficient vehicle for pathogenic microorganisms [7]. Ingestion of mud by racers who unintentionally swallow sufficient numbers of pathogens can cause illness, as described in the literature [2][3][4][5][6][7][8][9]. Over the last few years, outbreaks of acute gastroenteritis (AG) have been reported among participants in an obstacle race (with artificial obstacles) and in other endurance races that take place in nature (mountain bike races, triathlons) [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation